Legal Studies on Gender Changes Through Court Decisions on the Distribution of Inheritance (Comparative Study of Islamic Law and Civil Code) - Haldy Wiranda; Ahmad Fauzi; Tengku Erwinsyahbana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The legal consequences of gender changes seen from the positive legal side of gender changes actors are not hindered from obtaining inheritance rights from the testator. This is due to the fact that blood relations are an absolute requirement when it comes to obtaining inheritance rights. What also needs to be remembered is that gender changes is not a right that can prevent someone from getting their inheritance rights. Whereas gender changes in the distribution of inheritance according to the islamic law, the portion of the distribution of inheritance remains the same as the gender before gender changes operation. According to the civil code, gender changes has no effect on the distribution of inheritance for the person who undergoes gender changes. Moreover, the civil code does not comply with this at all. Whereas legal protection measures for people who carry out gender changes operation in obtaining a share of inheritance are by making regulations related to the legal consequences of gender changes operation.